Penerapan Pembelajaran Berbasis Proyek (PjBL) Berbantuan Media Educandy untuk Meningkatkan Hasil Belajar Kognitif IPS Siswa Kelas IV - Luthfia Azzahra; Ertina Koernia; Dyah Triwahyuningtyas (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
A problem identified in Social Studies learning among fourth-grade elementary school students was the low learning outcomes on the topic of cultural diversity. This problem was indicated by students’ limited engagement in the learning process and the less optimal use of learning models and instructional media that accommodated students’ learning characteristics. Based on this issue, this study aimed to improve the cognitive learning outcomes of fourth-grade students in Social Studies on the topic of cultural diversity through the implementation of the Project Based Learning (PjBL) model assisted by Educandy media. This study employed Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 24 students, consisting of 16 male students and 8 female students. Data were collected through achievement tests and documentation. The data were analyzed using both quantitative and qualitative descriptive approaches. The results showed that the implementation of the Project Based Learning (PjBL) model assisted by Educandy media improved students’ cognitive learning outcomes. The average score increased from 65.91 in the pre-cycle to 79.79 in Cycle I and 86.08 in Cycle II. The percentage of learning mastery also increased from 41.67% in the pre-cycle to 75% in Cycle I and reached 95.83% in Cycle II. Therefore, the Project Based Learning (PjBL) model assisted by Educandy media was proven to be effective in improving students’ cognitive learning outcomes in Social Studies learning at the elementary school level.